TBLT Task and Framework: Insights from Indonesian Context - Sukma, Doris (Journal of English Language Teaching, Literature and Culture, 2024)
This study employs a document study to investigate the tasks and TBLT framework used in Indonesian English classrooms. Through a rigorous examination of existing literature and empirical research, this study will elucidate how these practices contribute to the development of communicative competence, a core tenet of the Merdeka Curriculum. Several recent studies (past five years) on TBLT practices have been identified through a review of open-access journals. The findings reveal a prevalence of authentic tasks, consistent with expert recommendations, but with varying levels of authenticity. In addition, implementing TBLT generally aligns with established principles, particularly those proposed by Willis, but only a few adaptations are made to suit local teaching and learning goals. While these findings suggest a positive trend, further analysis is needed to identify potential areas for improvement and inform future TBLT practices in Indonesian classrooms.